Model Pembelajaran Kaiwa Tingkat Dasar sesuai dengan JF Standard - Astami, Timur Sri (Lingua Cultura, 2015)
Speaking competence a productive skills. However, the associated with teaching materials in the books Minna no Nihongo 1 renshuu C are expected discrepancy that competence in conversations class. That is can’t be fulfilled when referring to competence in according with JF Standard. So in this qualitative research to compare between the two textbooks Minna no Nihongo 1 with Marugoto A1 katsudou. Because the basic level of speaking competence indicator is able to perform a simple conversation, slowly and repeated, replacing the phrase, giving a help, being able to ask questions about important issues, and using daily topics in the basic conversation. And that should be a concern the purpose of making the material isn’t  the same as conversation learning with sentence patterns or grammar learning basically. And than  the books Minna no  Nihongo 1 renshuu C, that’s  material noticed how communication targets to be achieved in each meeting.